Clinical profile of end stage renal disease in patients on maintenance haemodialysis in a tertiary hospital (Journal of Gandaki Medical College-Nepal, 2020)
Introduction and Objectives: Chronic kidney disease is an increasing health problem worldwide and the burden of such patients is increasing in developing countries like Nepal as well. The final treatment for End Stage Renal Disease is only renal replacement therapy. The objective was to study the demographic and clinical profile of patients with End Stage Renal Disease undergoing haemodialysis.Methods: This was a prospective, observational study carried out in a tertiary hospital after obtaining ethical consent from the Institutional Review Board. The study period was from June 1st to August 31st, 2019. Thirty seven patients, older than 15 years who were on maintenance haemodialysis on regular basis in the hospital for at least 3 months were selected for the study. Patient’s records were used for the data collection as well as direct questionnaire to the patients on follow up for routine haemodialysis. Data were entered into Statistical Package for the Social Sciences 21 and descriptive analysis was done.Results: Twenty-six patients were under 50 years with male: female ratio of 1.64:1. Mean duration of haemodialysis of patients was 3.82 years. Most common cause for end stage renal disease was hypertension followed by idiopathic cause. Anaemia and hypocalcaemia were found to be the common complications associated with the patients.Conclusions: Prevention and early treatment may be the key to decrease the incidence of chronic kidney disease patients and also halt the progression to End stage renal disease.